HASIL BELAJAR MATEMATIKA BERDASARKAN KURIKULUM MERDEKA BELAJAR KELAS X DITINJAU DARI AKTIVITAS BELAJAR SISWA DI SMA NEGERI 2 GORONTALO PADA MATERI EKSPONENSIAL - Martya, Ananda; Ismail, Sumarno; Oroh, Franky Alfrits (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The purpose of this research is to describe the learning outcomes of tenth-grade students in mathematics subjects under the Kurikulum Merdeka Belajar by reviewing student learning activities on exponential material at SMA Negeri 2 Gorontalo. The method used in this study is descriptive qualitative, with the research sample being class X-11, where class distribution at SMA Negeri 2 Gorontalo is done evenly without regard to students' academic abilities. In this study, the instruments used for data collection include a questionnaire on student learning activities and tests on student learning outcomes in exponential material. The learning activities measured include visual activities, oral activities, writing activities, mental activities, and emotional activities, which are then identified into three categories of learning activity: high, medium, and low. For the learning outcome tests, four criteria are identified: emerging, adequate, proficient, and skilled, which are the completion criteria for learning objectives used in the independent learning curriculum.The results show that students with high learning activity consist of 5 students or 21%, with an average learning outcome of 49.5% classified as adequate; students with medium learning activity consist of 14 or 58%, with an average learning outcome of 42.58% also classified as adequate; and students with low learning activity consist of 5 students or 21%, with an average learning outcome of 45.42% classified as adequate. Based on the average positive responses regarding the learning activities of class X-11 students, four out of five indicators show low learning activity levels. This reflects that the average mathematics learning outcomes under the independent curriculum for exponential material are only at the adequate level, specifically at 44.6042%, indicating a need for improvement in several areas of exponential material. Thus, it is concluded that student learning activity plays a crucial role in mathematics learning outcomes under the independent curriculum, which is designed to create active student learning experiences.